Lean Six Sigma in Service Industries: Application, Challenges, and Best Practices - Maemunah, Siti; Teguh, Leo (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Lean Manufacturing with Six Sigma tools to improve efficiency and quality in various business processes. In the service industry, Lean Six Sigma has great potential for reducing waste, managing process variability, and increasing customer satisfaction. However, its implementation in the service sector faces unique challenges compared to manufacturing, due to the complexity of human interactions and high variability in service delivery. This research uses the PRISMA systematic approach to analyze and synthesize existing literature from various international databases. By identifying successful Lean Six Sigma best practices adaptation strategies, this research aims to provide insight into effective implementation strategies adapted to diverse service contexts, thereby increasing operational efficiency and overall service quality.